Philosophy of Science: Specific Methods, Elements, Structures, and Step for the Development of Knowledge Methodology - Sonda Winari; Azmi Fitrisia; Ofianto Ofianto (LEGAL BRIEF, 2022)
There is a close relationship between the philosophy of science and the development of the scientific method. Philosophy of science is an integral part of the history of the development of science. Philosophy of science is inseparable from scientific rules relating to the scientific method used. The scientific method will produce scientific knowledge as well . There are four special methods used, namely the library method, the observation method, the interview method, and the observer participation method. The elements in the methodology of science are interpretation, induction and deduction, internal correlation, holistic, historical continuity, idealization, comparison, heuristics, analogical, and description. Meanwhile the composition of the scientific methodology includes problems, attitudes, using scientific methods, activities, conclusions, and influences. The steps for developing scientific methodologies consist of formulating problems, conducting library studies, formulating hypotheses, testing hypotheses, collecting data, interpreting data, making conclusions, and making scientific reports.